Nitrogen addition decreased soil respiration and its components in a long-term fenced grassland on the Loess Plateau. (May 2018) - Wei, Lin; Su, Jishuai; Jing, Guanghua; Zhao, Jie; Liu, Jian; Cheng, Jimin; Jin, Jingwei
Abstract: Knowledge of the impact of N enrichment on soil respiration components is critical for understanding carbon (C) cycling and its feedback processes with climate change. We conducted three N level addition experiments, control (CK, 0 g N m −2 yr −1 ), low nitrogen addition (LN, 10 g N m −2 yr −1 ), and high nitrogen addition (HN, 20 g N m −2 yr −1 )) to investigate the response of microbial and root respiration to N enrichment in a long-term fenced grassland on the Loess Plateau of China. Compared to the control, both the LN and HN treatments generally decreased soil respiration and its two components for both years. Under N addition, the decreased rates of root respiration and microbial respiration were significantly and positively correlated with the monthly root production and soil microbial biomass C, respectively. Nitrogen addition decreased the Q10 values of root and microbial respiration, with the reduction more pronounced in root respiration. Overall, our results suggest that N enrichment may reduce the soil C loss through CO2 emissions. With global warming, soil C loss will be less due to the lower Q10 values of root and microbial respiration on the Loess Plateau of China under future scenarios of N deposition. Highlights: N addition decreased both microbial and root respiration in the long-term fenced grassland on the Loess Plateau. N addition led to a decrease in Q10 values for both soil respiration and its two components. The seasonal variation of soil respiration its components were closely related to soil moisture and plant growth. The interannual variation of soil respiration was related to the annual precipitation and its seasonal distribution.